Effects of Strong CYP2C8 or CYP3A Inhibition and CYP3A Induction on the Pharmacokinetics of Brigatinib, an Oral Anaplastic Lymphoma Kinase Inhibitor, in Healthy Volunteers - Tugnait, Meera; Gupta, Neeraj; Hanley, Michael J.; Sonnichsen, Daryl; Kerstein, David; Dorer, David J.; Venkatakrishnan, Karthik; Narasimhan, Narayana (Clinical pharmacology in drug development, 2020)
In vitro data support involvement of cytochrome P450 (CYP)2C8 and CYP3A4 in the metabolism of the anaplastic lymphoma kinase inhibitor brigatinib. A 3‐arm, open‐label, randomized, single‐dose, fixed‐sequence crossover study was conducted to characterize the effects of the strong inhibitors gemfibrozil (of CYP2C8) and itraconazole (of CYP3A) and the strong inducer rifampin (of CYP3A) on the single‐dose pharmacokinetics of brigatinib. Healthy subjects (n = 20 per arm) were administered a single dose of brigatinib (90 mg, arms 1 and 2; 180 mg, arm 3) alone in treatment period 1 and coadministered with multiple doses of gemfibrozil 600 mg twice daily (BID; arm 1), itraconazole 200 mg BID (arm 2), or rifampin 600 mg daily (QD; arm 3) in period 2. Compared with brigatinib alone, coadministration of gemfibrozil with brigatinib did not meaningfully affect brigatinib area under the plasma concentration‐time curve (AUC0–inf; geometric least‐squares mean [LSM] ratio [90%CI], 0.88 [0.83‐0.94]). Coadministration of itraconazole with brigatinib increased AUC0–inf (geometric LSM ratio [90%CI], 2.01 [1.84‐2.20]). Coadministration of rifampin with brigatinib substantially reduced AUC0–inf (geometric LSM ratio [90%CI], 0.20 [0.18‐0.21]) compared with brigatinib alone. The treatments were generally tolerated. Based on these results, strong CYP3A inhibitors and inducers should be avoided during brigatinib treatment. If concomitant use of a strong CYP3A inhibitor is unavoidable, the results of this study support a dose reduction of brigatinib by approximately 50%. Furthermore, CYP2C8 is not a meaningful determinant of brigatinib clearance, and no dose modifications are needed during coadministration of brigatinib with CYP2C8 inhibitors.